Demographic Change as a Strategic Signal in Aviation Services: Executive Sensemaking in Thailand - สุติญญามณี, วสวัตติ์; อมาตยกุล สมไร่ขิง, ธนิสา; รักเนตรสาคร, จุฬนี; บุณยเกียรติ, บุณยเกียรติ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aims to examine demographic structural change as a “Strategic Signal” in aviation services through the lens of executive sensemaking. An interpretive qualitative approach was employed. Data were collected through in-depth interviews with 18 senior executives in Thailand’s aviation industry and analyzed using thematic analysis.           The findings indicate that airline executives do not perceive demographic structural change merely as a structural constraint. Rather, they interpret it as a meaningful signal that shapes strategic priorities in four key areas: (1) designing travel experiences for aging passengers, (2) service-based risk management and safety assurance, (3) managing and retaining experienced frontline employees, and (4) integrating digital technologies with human-centered service. This study contributes to the literature on aviation service strategy by expanding theoretical understanding of demographic change as a strategic signal and offering important insights for airline management in the context of an aging society.